Flyways To De-Congest Data Center Networks - Kandula, Srikanth; Padhye, Jitu; Bahl, Victor (2009)
A study of application demands from a production datacenter of 1500 servers shows that except for a few outliers, application demands can be generally met by a network that is slightly oversubscribed. Eliminating oversubscription is hence a needless overkill. In a significant departure from recent proposals that do so, we advocate a hybrid architecture. The base network is provisioned for the average case, is oversubscribed, and can be built with any of the existing network designs. To tackle the hotspots that remain, we add extra links on an on-demand basis. These links called flyways provide additional capacity where and when needed. Our results show that even a few additional flyways substantially improve performance (by over 50%), as long as they are added at the right place in the network. We consider two design alternatives for adding flyways at negligible additional cost: one that uses wireless links (60ghz or 802.11n) and another that uses commodity switches to add capacity in a randomized manner.